Analisis Persepsi Mahasiswa Pendidikan Kimia Terhadap Kualitas Laboratorium Kimia Kampus - Lathifah, Arini Izzataki; Dwi M, Habstianing; Siti Fauziah, Endah; Suryani, Elma; Lisdiana, Hayyun (LPPM Universitas Negeri Jakarta, 2023)
This study aims to analyze the perceptions of Chemistry Education students toward chemistry laboratories on campus. Researchers used the Chemistry Laboratory Environment Inventory (CLEI) questionnaire to identify student perceptions. In the questionnaire, students must assess the actual conditions of the laboratory with their ideal laboratory. This study involved 70 Chemistry Education students from four different levels. Based on the results of the questionnaire, the researcher selected one student at each level to be interviewed. The interview aims to determine more about the degradation of student perceptions at each level about the state of the chemistry laboratory FMIPA UNJ. The CLEI instrument is considered reliable and can be used for further research. The results also show that there is no significant difference between student's perceptions of the actual quality of the laboratory and the ideal conditions they expect. There is also no difference in perception between first-year students and fourth-year students. The results of this study are expected to contribute to improving the quality of a better chemistry laboratory.